EFEKTIVITAS PENDIDIKAN DAN PELATIHAN DALAM MENINGKATAN KINERJAAUDITOR DI INSPEKTORAT KABUPATEN LAMONGAN PROVINSI JAWA TIMUR - Sukmana, Ely (Fakultas Politik Pemerintahan, 2019)
Effectiveness of Education and Training in Increasing Auditor Performance at the Lamongan Regency Inspectorate of East Java Province. This study aims to find out and analyze education and training to be the driving factors for improving the performance of auditors at the Inspectorate of Lamongan Regency, East Java Province. The researcher used a qualitative descriptive method with an inductive approach. The conclusion of this study is the effectiveness of education and training carried out through technical training programs held by the Lamongan District Inspectorate and the implementation of functional training and technical training outside which aims to improve the performance of the Lamongan District Inspectorate auditors, including being effective. This can be understood from the results of the overall study through interviewing the author with sources and direct observations. The indicators of effectiveness of auditor participation to carry out technical training carried out by the Inspectorate and functional training and technical training held outside of stating that, every implementation. Education and training can have a positive impact on the auditor of the Lamongan District Inspectorate in improving performance to carry out their duties and functions as internal government supervisors.